SYNERGY BETWEEN PARENTS AND TEACHERS IN MOTIVATING CHILDREN'S LEARNING DURING THE COVID-19 PANDEMIC - Arinda Alifia; Susi Ratnawati; Tri Prasetijowati (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2022)
This study aims to analyze the synergy between parents and teachers in motivating children's learning enthusiasm in the era of the covid-19 pandemic. This synergy is a collaboration carried out by parents and teachers for elementary school children in motivating children's enthusiasm for learning in this era of the covid-19 pandemic. Parents are required to play an important role in motivating children to facilitate a learning process. Meanwhile, teachers are required to be more creative in the learning process so that children are motivated to learn in the era of the COVID-19 pandemic. This study uses a qualitative method. The results obtained from this study are that in the implementation of this synergy it brings positive results to the motivation of learning enthusiasm for elementary school children in the city of Surabaya. The synergy carried out by parents and teachers also encountered an obstacle. The obstacles that occur are caused by internal factors and external factors on the motivation of children's learning enthusiasm. With the obstacles from synergy, of course, parents and teachers must make efforts to overcome the inhibiting factors of synergy to motivate children's learning enthusiasm. The efforts made must also be effective and efficient for a child. Keywords: Energy; Parents; Teachers; Motivation; Pandemic.